Interactive effects of host plant and insecticide foliar application on oviposition and performance of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) cryptic species Mediterranean (MED) and Middle East-Asia minor 1 (MEAM1) in Brazil - Libardi Miraldo, Leonardo [UNESP]; Malaquias, José Bruno [UNESP]; Oliveira de Freitas Bueno, Regiane Cristina [UNESP] (Springer Nature, 2021)
The Bemisia tabaci (Gennadius) cryptic species complex is composed of important pest insects, with cryptic species Mediterranean (MED) and Middle East-Asia Minor 1 (MEAM1) having caused severe yield reduction on crops worldwide. The former was reported in Brazil in 2014, while the latter was first reported in the country in the 1990s. Although farmers have highly adopted insecticide application for B. tabaci management, its efficacy may vary among host plants and cryptic species. Cyantraniliprole is a new anthranilic diamide insecticide with a mode of action that activates the insect ryanodine receptor (RyR). In this context, the purpose of this study was to investigate the effects of cyantraniliprole spraying on the oviposition and performance of MEAM1 and MED cryptic species in tomato and sweet pepper plants. Cyantraniliprole caused high adult mortality for both cryptic species on sweet pepper (> 94%), while its efficacy was moderate for MEAM1 (~ 56%) and low for MED (~ 12%) on tomato. MED laid more eggs on sweet pepper and tomato treated with water and cyantraniliprole, respectively, than MEAM1. Additionally, cyantraniliprole reduced the hatchability of MED and MEAM1 on sweet pepper and tomato, respectively. Moreover, MED showed better performance than MEAM1 regardless of the treatment and host plant, except on tomato treated with water. Our results indicate that cyantraniliprole efficacy changes according to B. tabaci cryptic species and host plant. These findings will be important for redesigning cyantraniliprole doses for B. tabaci management in Brazil.
Keywords: B-biotype; Cyantraniliprole; Q-biotype; Sweet pepper; Tomato; Whitefly